Analysis of Teaching Materials based on the Integration of Science and Technology in Improving the Learning Process of Islamic Education in Grade X Students of Madrasah Aliyah An-Nur Rambipuji Jember - Shidiq Shidiq; Muh. Fiqih Shofiyul Am; Masduki Masduki; Muhammad Yusron Maulana El-Yunusi; Dubois Benoit (Pengabdian: Jurnal Abdimas, 2023)
Background. PAI learning tends to focus on abstract concepts that feel far from everyday life, making it difficult for students to interpret and understand the values in PAI learning. Therefore, it is very important for teachers to prepare and pay attention to teaching materials well, because this has a significant influence on improving the quality and competence of students.. Purpose. The ultimate goal of this research is to improve the quality of PAI learning and provide a more holistic understanding to students or learners. By gaining a more complete and integrated understanding of religion, science and technology, it is expected that students will be able to better integrate this knowledge in their daily lives. This will help students make better decisions, solve complex problems, and face modern challenges with a richer and deeper understanding. Method. the type of research is research (research) and development (development), while the research model is descriptive development through the ADDIE development model, namely analyzing, designing, developing, implementing and evaluating. Results. The development of PAI teaching materials based on science and technology integration in class X M.A An nur Rambipuji Jember is still not running optimally, and effectively so that there needs to be special guidance to educators, so that PAI teaching materials based on science and technology integration can run more effectively. Conclusion. Science and technology cannot be separated in Islamic education learning in educational institutions, so from it, there is a need for improvement and optimization regarding the development of science and technology-based Islamic religious education (PAI) teaching materials, with science and technology-based teaching materials the institution will get the expected results or goals, because currently formal institutions must be prepared with advances in technology and science which are increasingly becoming an interest for students and are also able to compete with the increasing number of other formal institutions.